2005
DOI: 10.1103/physrevlett.95.075301
|View full text |Cite
|
Sign up to set email alerts
|

Observation of Surface Andreev Bound States of SuperfluidHe3by Transverse Acoustic Impedance Measurements

Abstract: Complex transverse acoustic impedance of the superfluid (3)He-B was measured at the frequencies of 10 to 80 MHz at 17.0 bar by a cw bridge method. The observed temperature dependence was well explained by the quasiclassical theory with random S-matrix model for a diffusive surface. The temperature dependence was influenced by pair breaking and by quasiparticle density of states at the surface, which was drastically modified from the bulk one by the presence of surface Andreev bound states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(81 citation statements)
references
References 23 publications
2
79
0
Order By: Relevance
“…At the weak coupling limit, the planar is energetically degenerate to the A-phase that is the time-reversal symmetry breaking phase with point nodes, while the strong coupling effect that is the spin-fluctuation feedback effect can stabilize the A-phase relative to the planar phase and the A-B phase boundary becomes the first order transition. The pair breaking effect and the enhancement of the surface density of states due to the surface bound state have been observed by several experiments, by using the NMR techniques [112,113,114,115,116,117,118,155,156,157], the motion of a vibrating wire resonator [158], transverse acoustic impedance [162,163,164,165,166,167,168,169], surface contributions of the heat capacity [160], and anomalous attenuation of transverse sound [161]. Among them, Murakawa et al [165,168] has observed the specularity dependence of the surface density of states by systematically controlling the surface specularity by coating the surface with 4 He layers.…”
Section: Thermodynamics In the Absence Of Dipole-dipole Interactionmentioning
confidence: 99%
See 3 more Smart Citations
“…At the weak coupling limit, the planar is energetically degenerate to the A-phase that is the time-reversal symmetry breaking phase with point nodes, while the strong coupling effect that is the spin-fluctuation feedback effect can stabilize the A-phase relative to the planar phase and the A-B phase boundary becomes the first order transition. The pair breaking effect and the enhancement of the surface density of states due to the surface bound state have been observed by several experiments, by using the NMR techniques [112,113,114,115,116,117,118,155,156,157], the motion of a vibrating wire resonator [158], transverse acoustic impedance [162,163,164,165,166,167,168,169], surface contributions of the heat capacity [160], and anomalous attenuation of transverse sound [161]. Among them, Murakawa et al [165,168] has observed the specularity dependence of the surface density of states by systematically controlling the surface specularity by coating the surface with 4 He layers.…”
Section: Thermodynamics In the Absence Of Dipole-dipole Interactionmentioning
confidence: 99%
“…The contributions of surface Andreev bound states have also been detected through the deviation of the heat capacity from that in the bulk 3 He-B [160] as well as the anomalous attenuation of transverse sound wave [161]. The surface acoustic impedance measurement provides another powerful tool to probe the surface structure [162,163,164,165,166,167,168]. The spectrum of the surface bound states and its dependence on surface condition has been investigated by measuring surface acoustic impedance [165,168,169].…”
Section: 3mentioning
confidence: 99%
See 2 more Smart Citations
“…21) We have demonstrated in earlier publications that Z is a unique surface probe for SABS in superfluid 3 He and have provided the spectroscopic details of SDOS. 17,[21][22][23] Figure 2 presents the measured ZðT Þ as a function of the normalized energy h " !=ÁðT Þ. ÁðT Þ is the superfluid gap energy at T obtained from the weak-coupling-plus model; 12) thus, a higher (lower) energy corresponds to a higher (lower) temperature. Z 0 is the normal state value of Z just above the transition temperature T c .…”
mentioning
confidence: 99%